Implementasi Implementasi Model Pembelajaran Problem Based Learning Pada Mata Pelajaran Instalasi Motor Listrik - Yuki Ardhana Santosa; Aswardi Aswardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
This research is motivated by the low student learning outcomes in the subject of electric motor installation. Learning that takes place in the classroom is still conventional, generally using the lecture method and writing learning materials on the blackboard. Students or students listen to the teacher's explanation while writing learning material in front of the class. This study aims to determine the effectiveness of the implementation of the Problem Based Learning (PBL) model on Electrical Motor Installation Subjects at SMK Muhammadiyah Padang. This study uses a quantitative approach with the type of Pre-Experimental using a one class posttest design. The subjects of this study were students of the Muhammadiyah 1 Padang vocational high school majoring in electrical energy installation engineering, totaling 22 people. The population in this study means that all students of class XI, Department of Electrical Energy Installation Engineering, Muhammadiyah 1 Padang Vocational High School. The research data processing uses the SPSS application which illustrates that the posttest scores obtained by students are the lowest score of 63 and the highest of 100. The results show that the average posttest score after applying the Problem Based Learning model is 85.6. The result of classical completeness test is 86.36%. This means that it is concluded that the Problem Based Learning (PBL) learning method is said to be very effective because it can be seen from the higher classical completeness value of 85%, which is 86.36%.